The Practicality of Interactive Learning Media Based on Android Applications in the Concept of Human Respiratory System for High School - Candra Pratama b; Kaspul Kaspul; Muhammad Arsyad (Inovbook Publications, 2022)
An important source of learning in the millennial era is interactive learning media that can be accessed via smartphones. Development research that produces a practical Android learning media. This type of research was adapted from Tessmer's design, through initial preparation (preparation) and formative evaluation (formative evaluation). The practicality of the contents of 5 students of class XI MIPA 2 through individual tests. The subject of practicality is the expectation of 9 students of Class XI MIPA 2 through a small group test. Data obtained from research instruments consisted practicality of contents, and practicality of expectations. The technique of approving data uses approved sheets. Practicality based on the Akbar & Sriwiyana category (2010). This media obtained practicality of contents 88.00%, and practicality of expectations 96.30%, so that it was included in the category of very practical